Functionally significant metabolic differences between B and T lymphocyte lineages. Issue 2 (26th August 2019) - Khalsa, Jasneet Kaur; Chawla, Amanpreet Singh; Prabhu, Savit B.; Vats, Mukti; Dhar, Atika; Dev, Gagan; Das, Nabanita; Mukherjee, Sandip; Tanwar, Shalini; Banerjee, Hridesh; Durdik, Jeannine Marie; Bal, Vineeta; et al.
Summary: Activation of B and T lymphocytes leads to major remodelling of the metabolic landscape of the cells enabling their post‐activation functions. However, naive B and T lymphocytes also show metabolic differences, and the genesis, nature and functional significance of these differences are not yet well understood. Here we show that resting B‐cells appeared to have lower energy demands than resting T‐cells as they consumed lower levels of glucose and fatty acids and produced less ATP. Resting B‐cells are more dependent on OXPHOS, while T‐cells show more dependence on aerobic glycolysis. However, despite an apparently higher energy demand, T lineage cells showed lower rates of protein synthesis than equivalent B lineage stages. These metabolic differences between the two lineages were established early during lineage differentiation, and were functionally significant. Higher levels of protein synthesis in B‐cells were associated with increased synthesis of MHC class II molecules and other proteins associated with antigen internalization, transport and presentation. The combination of higher energy demand and lower protein synthesis in T‐cells was consistent with their higher ATP‐dependent motility. Our data provide an integrated perspective of the metabolic differences and their functional implications between the B and T lymphocyte lineages. Abstract : B and T cells are closely related, yet functionally distinct subsets of the immune system and little is known about the metabolic distinctions that can help explain this functional dissimilarity. These metabolic differences are established early during lineage differentiation resulting in naïve T cells that rely more on glycolysis and have high ATP levels that explains their higher motility important for scanning cells to find their cognate antigen. In contrast, B cells rely more on oxidative phosphorylation and have high rate of protein synthesis associated with increased expression of antigen processing and presentation proteins pertinent to the role of B cells as antigen presenting cells.